2019
DOI: 10.5505/tjo.2019.1903
|View full text |Cite
|
Sign up to set email alerts
|

Taste Alteration in Cancer Patients Receiving Chemotherapy: A Cross-Sectional Study

Abstract: This study aimed to investigate nutrition in cancer patients, chemotherapy-induced taste alterations and the factors affecting these taste alterations. METHODS This study was planned as a cross-sectional study. Patients who had received chemotherapy at least once and had been on chemotherapy for the last 7-10 days (n=112) were included in this study. The data were collected using the Patient-Generated Subjective Global Assessment, the National Cancer Institute's Common Terminology Criteria for Adverse Events a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
2
6
0
2
Order By: Relevance
“…According to our results, a higher mean score on the taste disorder subscale suggested a higher risk of malnutrition. The taste disorder or discomfort subscale assesses the link between changes in taste sensation and nausea or vomiting, changes in the sense of smell, difficulty eating hot food, fatty food, meat, and appetite loss [ 12 ]. As a result, taste problems were assumed to have a serious effect on eating behavior and food selection, raising the risk of malnutrition, and making taste disorder an important determinant of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our results, a higher mean score on the taste disorder subscale suggested a higher risk of malnutrition. The taste disorder or discomfort subscale assesses the link between changes in taste sensation and nausea or vomiting, changes in the sense of smell, difficulty eating hot food, fatty food, meat, and appetite loss [ 12 ]. As a result, taste problems were assumed to have a serious effect on eating behavior and food selection, raising the risk of malnutrition, and making taste disorder an important determinant of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers and older patients were less affected by chemotherapy-induced taste impairments due to their increased taste thresholds [ 2 , 10 ]. On the other hand, women were found to be more susceptible to dysgeusia than men [ 11 , 12 ]. Developing dysgeusia was significantly associated with the type of cancer and the chemotherapy regimen [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study that was carried out by Celik et al (n=196), it was found that patients experienced moderate levels of taste changes, as well as moderate levels of phantogeusia and parageusia among types of taste change (25). In other studies using CiTAS and examining taste changes in different types of cancer, CiTAS subscale scores have usually been reported in the range of 1-3 (7,26,27). In addition to the direct physiological effects of chemotherapy, other symptoms of the disease itself and the adverse effects of chemotherapy also affect the sensation of taste.…”
Section: Discussionmentioning
confidence: 99%
“…Benzer olarak Akciğer kanserli hastalarda yapılan bir çalışmada, tat değişikliği ile kanser tipi, evresi, hastalık süresi, kemoterapi protokolü arasında bir ilişki olmadığı bildirilmiştir (21). Farklı tip kanser tanısı olan hastalarda CiTAS ölçeğinin kullanılarak tat değişikliğinin değerlendirildiği çalışmalarda da hastaların hastalık süresine, kanser evresine, kanser tipine ve kemoterapi tipine göre tat değişikliği skorlarının farklılık göstermediği belirlenmiştir (29,31).…”
Section: Verilerin Toplanmasıunclassified
“…Bu çalışmada da hastalar orta şiddette tat değişikliği yaşarken, tat değişikliğine bağlı rahatsızlığı da orta şiddette deneyimlediği belirlenmiştir. CiTAS ölçeğinin kullanılarak farklı kanser tip tanısı olan hastalarda tat değişikliğinin değerlendirildiği çalışmalarda genellikle hastaların CiTAS ölçeğinin alt boyut puan skorları 1 ile 3 arasında değişiklik göstermiştir (29)(30)(31). Diğer çalışma sonuçlarından da kemoterapi alan kanserli hastalarda tat değişikliği niteliğinin farklı yoğunlukta ve farklı sıklıkta olabildiği anlaşılmaktadır (9, 23,24).…”
Section: Verilerin Toplanmasıunclassified